A survey on the soundscape perception before and during the COVID-19 pandemic in Italy - Bartalucci Chiara (Noise Mapping, 2021)
At the time of the COVID-19 pandemic, the impact of lockdown measures highlights changes in terms of sounds and noises present in the everyday life. The present paper deals with this peculiar and unexpected scenario as studied by means of an online survey consisting of 18 questions and distributed to residents in the Italian territory. For studying the unprecedented effect of the pandemic, participants were asked to fill the questionnaire, providing personal data, describing context and characteristics of the house in which they live and making a comparison of the lockdown soundscape with the pre-lockdown one. About four hundred questionnaires have been collected and analysed in order to define correlations between personal and perception variables. Using logistic regression models, changes have been studied during the two abovementioned periods. It has been observed that the perception of traffic noise has increased for people over 35 years old and the noise produced by the neighbourhood has been more statistically significant for employed respondents. Future outlook might provide the spread of the questionnaire in other countries for a global evaluation of the data, to be also acquired with reference to the after-lockdown period.